2002
DOI: 10.1124/jpet.301.1.306
|View full text |Cite
|
Sign up to set email alerts
|

ς2-Receptor Regulation of Dopamine Transporter via Activation of Protein Kinase C

Abstract: The elucidation of the mechanisms underlying 2 -receptor activation and signal transduction is crucial to the understanding of 2 -receptor function. Previous studies in our laboratory have demonstrated 2 -receptor-mediated regulation of the dopamine transporter (DAT) as measured by amphetamine-stimulated release of [ -Receptors were first identified in 1976 by Martin et al. (1976) as the sites through which the psychotomimetic effects of SKF10,047 were mediated. Since that time, progress in identifying their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 36 publications
3
35
0
Order By: Relevance
“…GF109203x, a PKC inhibitor, abolished 2 receptor-mediated regulation of dopamine transporter activity (Derbez et al, 2002). Morin-Surin et al (1999) showed a parallel translocation of receptors and PKC␤I and PKC␤II from the cytosol to the plasma membrane upon agonist application.…”
Section: Discussionmentioning
confidence: 99%
“…GF109203x, a PKC inhibitor, abolished 2 receptor-mediated regulation of dopamine transporter activity (Derbez et al, 2002). Morin-Surin et al (1999) showed a parallel translocation of receptors and PKC␤I and PKC␤II from the cytosol to the plasma membrane upon agonist application.…”
Section: Discussionmentioning
confidence: 99%
“…First, during cocaine-induced sensitization, there are changes in the dopamine transporter and dopamine levels in the brain (54). Sigma receptors have been known to modulate dopamine transporter function and dopamine release via protein kinase C, the calcium/calmodulin-dependent kinase II system, ceramide, and changes in calcium levels (36,55,56). Second, activation of σ receptors can indirectly increase phosphorylation of CREB via ceramide, which is an important mediator of neuroadaptations in the brain (57)(58)(59).…”
Section: Discussionmentioning
confidence: 99%
“…Treated n PMA (1 M) 9.5 Ϯ 0.90 10.6 Ϯ 1.5 3 Chelerythrine (5 M The relationship of receptor activation to Ca 2ϩ changes and IP 3 turnover, as well as evidence from our own laboratory demonstrating the abolition of 2 receptor-mediated regulation of dopamine transporter activity by the PKC inhibitor GF109203x (Derbez et al, 2002) suggests that the PKC signaling system could participate in 1 receptor-mediated regulation of vesicular dopamine release. PKC has been implicated in enhancement of release of other neurotransmitters (Majewski and Iannazzo, 1998), including adenosine and norepinephrine.…”
Section: Controlmentioning
confidence: 99%
“…We reasoned that if receptors required an intact PKC signaling pathway, disruption of the pathway using PKC inhibitors should block the ability of receptor agonists to regulate stimulated [ 3 H]dopamine release. We have previously shown that 2 receptors were linked to dopamine transporter function via activation of a Ca 2ϩ -dependent PKC isozyme (Derbez et al, 2002). …”
mentioning
confidence: 99%